Co-Existence of Two Multidrug-Resistant Non-Fermenter Gram-Negative Bacilli: The Dead End or is There Still Hope? - Edavaloth , Preethy; Mukhida, Sahjid; Kannuri, Sriram; Shah, Heer; Datta, Amitesh (National Journal of Community Medicine, 2023)
NA